Heterogeneous Catalysis for Water Oxidation by an Iridium Complex Immobilized on Bipyridine‐Periodic Mesoporous Organosilica. (11th May 2016) - Liu, Xiao; Maegawa, Yoshifumi; Goto, Yasutomo; Hara, Kenji; Inagaki, Shinji
Abstract: Heterogenization of metal‐complex catalysts for water oxidation without loss of their catalytic activity is important for the development of devices simulating photosynthesis. In this study, efficient heterogeneous iridium complexes for water oxidation were prepared using bipyridine‐bridged periodic mesoporous organosilica (BPy‐PMO) as a solid chelating ligand. The BPy‐PMO‐based iridium catalysts (Ir‐BPy‐PMO) were prepared by postsynthetic metalation of BPy‐PMO and characterized through physicochemical analyses. The Ir‐BPy‐PMOs showed high catalytic activity for water oxidation. The turnover frequency (TOF) values for Ir‐BPy‐PMOs were one order of magnitude higher than those of conventional heterogeneous iridium catalysts. The reusability and stability of Ir‐BPy‐PMO were also examined, and detailed characterization was conducted using powder X‐ray diffraction, nitrogen adsorption, 13 C DD MAS NMR spectroscopy, TEM, and XAFS methods.